Epistemology of e-democracy and e-governance through scientific mapping - Esther García-Río; Pedro Baena-Luna (Tourism & Management Studies)
This paper aims to address the current limitations in knowledge about e-democracy by establishing the conceptual, intellectual, and social structure of scientific literature. Hence, this paper offers an in-depth bibliometric analysis of the literature that has addressed this reality since its first publication in 1983. The most important scientific databases currently used in the academic field were consulted to achieve this objective: Web of Science (WoS) and Scopus. In the case of WoS, 540 articles were identified, 572 in the case of Scopus. The results were harmonised to obtain a final 773 articles under study. This harmonisation of results from different databases is a differential element concerning other studies in which the analysis was carried out on a single database, thus reducing a global and homogeneous vision of the possible connections and interrelationships of the realities analysed. The information collected has been processed using the Bibliometrix tool, which provides information on annual scientific production, authors, journals, topics, keywords, etc. The processing and analysis of the results has made it possible to identify research trends in the area, establish relationships between them and detect future research opportunities for the e-democracy phenomenon.